Effectiveness of a teletherapy-based phonological short-term memory training in reducing phonological impairments in the logopenic variant of primary progressive aphasia: a multiple case study - Duboisdindien, Guillaume; Lavoie, Monica; Laforce, Robert; Macoir, Joel (Frontiers in Human Neuroscience, 2025)
The logopenic variant of Primary Progressive Aphasia (lvPPA) is marked by phonological short-term memory deficits that compromise repetition and communication. While previous interventions in PPA have primarily targeted lexical-semantic abilities, little is known about therapies that directly address phonological impairments, primarily through teletherapy. This first study investigated the efficacy of an intensive phonological short-term memory training program delivered via teletherapy in individuals with the lvPPA. The intervention aimed to improve repetition of trained items, promote generalization to untrained items, facilitate transfer to functional tasks, and ensure maintenance over time. In the present study, significant improvements were observed in both immediate and delayed repetition of trained items, with partial short-term generalization to untrained items, particularly for words in delayed tasks. No substantial generalization effects were observed for functional language tasks, including picture description and picture naming, suggesting that the intervention’s impact may remain task specific. Individual trajectories revealed heterogeneous responses, potentially influenced by baseline cognitive profiles, spontaneous strategies, or fatigue. Mixed-effects models confirmed that interindividual factors explained a substantial portion of the variance. These findings support the feasibility and clinical relevance of remote phonological training in the lvPPA and underline the importance of early, personalized interventions. The study also raises the hypothesis that delayed repetition may facilitate internal rehearsal, enhancing generalization. Further research is needed to assess broader functional outcomes and optimize protocol scalability.